Prognostic Effect of Primary Recurrence Patterns in Squamous Cervical Carcinoma After Radical Surgery - Zhang, Zongkai; Jiang, Long; Bi, Rui; Wu, Xiaohua; Ke, Guihao; Zhu, Jun (Frontiers in Oncology, 2022)
Objective: To examine the effect of primary recurrence patterns on the prognosis of squamous cervical cancer after initial treatment. Methods: Primary recurrence patterns and prognostic factors were examined in stage IB-IIA cervical cancer patients after initial treatment. Recurrence site (locoregional recurrence and distant metastasis or in-field and out-field recurrence for patients receiving adjuvant radiotherapy) and subtype (nodal and organ recurrence) were examined. Clinicopathological characteristics and survival rates were evaluated to generate a prognostic nomogram. Results: A total of 472 patients were included. The median follow-up period, 5-year overall (OS) rate, and median OS were 59.1 months, 33.7%, and 24.0 months, respectively. Overall, 38.8% and 61.2% of the patients had locoregional recurrence and distant metastasis, respectively, and survival rates were comparable in these groups. Patients with nodal recurrence had better OS than those with organ recurrence (38.3% vs 30.7%, respectively; P = 0.001). Patients not receiving adjuvant radiotherapy had increased risk of pelvic recurrence (odds ratio [OR] = 0.148; 95% confidence interval [CI]: 0.075–0.291, P = 0.000). Positive lymph-vascular space invasion (OR= 1.928; 95% CI: 1.151–3.229, P = 0.013) and no chemotherapy (OR = 0.521; 95% CI: 0.317–0.733, P = 0.040) increased the risk of distant metastasis. Positive lymph node status after initial treatment were associated with nodal recurrence (OR = 3.729; 95% CI: 1.838–7.563, P = 0.000), while elevated preoperative squamous cell carcinoma antigen (SCC-Ag) levels were associated with organ recurrence (OR = 1.642; 95% CI: 1.325–2.265, P = 0.002). Recurrence subtype, therapy for relapse, the International Federation of Gynecology and Obstetrics stage, adjuvant radiotherapy, preoperative SCC-Ag levels, and risk subgroup were independently associated with OS. Conclusions: Primary recurrence patterns were associated with specific clinicopathological characteristics of cervical cancer. Recurrent cervical cancer prognosis was mainly affected by recurrence location and subtype.